HUBUNGAN DUKUNGAN KELUARGA DENGAN KEJADIAN MALARIA DI DESA DUMATI KECAMATAN TELAGA BIRU KABUPATEN GORONTALO TAHUN 2013 - Mohammad Hadi; Firmawati Firmawati (-, 2021)
Malaria is an infectious disease which has global concern. It is considered to be a public health problem by affecting the increase of the mortality and morbidity rate of infant, children under five, and pregnant women. It also reduces the productivity of human resources. The number of cases of malaria in Dumati Village, Telaga Biru District was 81. From 15 villages in Telaga Biru District, Dumati Village was considered as the highest case village in the work area of Tuladenggi Medical Center. The purpose of this study is to determine the relationship between the support from family and the cases of malaria in Dumati Village, Telaga Biru District in 2012. The type of this study was Correlation Descriptive by using Cross Sectional Study approach. The samples in this study were 152 respondents. Sampling technique used was quota sampling. The data was collected by using a questionnaire to obtain information from respondents about family support against case of malaria. The results were statistically tested with Chi Square test using SPSS version 17.0. The result of the study showed the value of X² (3.180) and sig (0.075) which is greater than alpha (0.05) indicating that there is no significant relationship between the family support and the case of malaria in Dumati Village, Telaga Biru District.